Monetary Policy and Relative Price Shocks in South Africa and Other Inflation Targeters - Cuevas, Alfredo (IMF Working Papers; Working Paper ;, 2008)
When faced with a relative price shock, monetary authorities often aim to contain its second round effects on inflation while accepting first round effects. We analyze the experience of South Africa and other inflation targeters to explore whether and when this policy prescription implies changing the monetary policy stance. Inflation targeting central banks differ on how aggressively they typically react to relative price shocks, reflecting differences in resilience of underlying inflation to such shocks. An examination of individual policy decisions reveals the importance of the broader economic context in framing the responses to relative price shocks.